Adaptation and the cost of rising temperature for the U.S. economy - François Gourio; Charles Fries (Federal Reserve Bank of Chicago, 2020)
How costly will rising temperature due to climate change be for the U.S. economy? Recent research has used the well-identified response of output to weather to estimate this cost. But agents may adapt to the new climate. We propose a methodology to infer adaptation technology from the heterogeneous responses of output to weather observed currently across the U.S. Our model estimates how much each region has adapted already, and can predict how much each will adapt further after climate change. The size and distribution of losses from climate change vary substantially once adaptation is taken into account.
Keywords: 330; Arbeitsproduktivität; Produktivität; Messung; Statistische Methode; Theorie; Großbritannien